3D hierarchical mesoporous NiCo2S4@Ni(OH)2 core–shell nanosheet arrays for high performance supercapacitors. (5th April 2016) - Nguyen, Van Hoa; Lamiel, Charmaine; Shim, Jae-Jin
Abstract : A thin and porous active material on a carbon cloth was synthesized by electrodeposition and its electrochemical performance was studied. Abstract : Hierarchical mesoporous NiCo2 S4 @Ni(OH)2 core–shell nanosheet arrays on conductive carbon substrates were prepared using a facile electrochemical deposition method and used as electrodes for supercapacitors. These electrodes exhibited rapid electron and ion transport, and excellent structural stability due to the highly conductive and mesoporous nature of the carbon substrates and NiCo2 S4 @Ni(OH)2 nanosheets, as well as due to the open framework of the three-dimensional nanoarchitectures. The capacity of the obtained electrodes was as high as 15.7 mA h cm −2 at a high current density of 100 mA cm −1, highlighting their promising applications as efficient positive electrodes for electrochemical capacitors.